2019
DOI: 10.1007/s12273-019-0539-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the impact of presence patterns on energy demand in residential buildings using measured data and simulation models

Abstract: Prediction of the energy performance of buildings helps designers with decision-making during the design process in new construction, as well as in renovation projects. Simulation software is used as a prediction tool to calculate the energy performance of buildings. However, numerous studies question its reliability due to the existing discrepancy (gap) between calculated and actual energy performance. Although occupant behaviour is identified as a factor of major impact on the energy performance of buildings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 27 publications
0
22
0
1
Order By: Relevance
“…For single-family houses, the number of investigated buildings was equally distributed in the range between 1 and 10 as well as 11 and 100, with few studies above 100 [75,76]. The only other building-related information was dwelling size, reported by few studies [17,77]. It can be concluded that the resolution of available information on the investigated buildings tends to be low.…”
Section: Basic Characteristics Of the Studies' Objectsmentioning
confidence: 97%
See 2 more Smart Citations
“…For single-family houses, the number of investigated buildings was equally distributed in the range between 1 and 10 as well as 11 and 100, with few studies above 100 [75,76]. The only other building-related information was dwelling size, reported by few studies [17,77]. It can be concluded that the resolution of available information on the investigated buildings tends to be low.…”
Section: Basic Characteristics Of the Studies' Objectsmentioning
confidence: 97%
“…The characteristics reported are generally inconsistent across the studies due to differences in research foci and data availability issues. The most reported characteristics are the number of people [9,10,15,26,33,49,59,60,[79][80][81], age [9,10,15,17,21,26,33,59,77,80,81], household composition [6,7,12,14,17,30,59,77,80,82,83], and income [9,10,21,26,29,33,79,80]. Additional characteristics reported were ownership status [9,10,26,79,80,84] and education levels [17,21,…”
Section: Basic Characteristics Of Occupants In the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the occupancy dynamics of the building, with other previously mentioned building variables creates knowledge that can be used for tasks such as energy, space and facility management, or even as an aid to the organisation's human resources department. For example, in the field of building simulation, occupant behaviour was recognised as a significant factor contributing to the high discrepancy between simulation prediction and real energy use [5][6][7][8]. Furthermore, Tianzhen et al [9] have listed ten challenges of building simulations where information on occupancy schedule is directly affecting three of them (addressing the building performance gap, modelling human-building interactions and energy model calibration).…”
Section: Introductionmentioning
confidence: 99%
“…Their work has tried to infer binary occupancy status (present, not present) and ranged occupancy (range of the number of present occupants). Since in the lab, the maximum occupancy is twelve persons, the authors have divided occupancy into four bins (0, 1-2, 3-5, [6][7][8][9][10][11][12]. Authors have used the following classifiers: NaiveBayes, Random Forest, Decision Tree, Multilayer Perceptron and KNN.…”
Section: Introductionmentioning
confidence: 99%